STRATEGI PENGEMBANGAN KLINIK MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALISIS MENURUT PERSEPSI PASIEN(STUDI KUALITATIF DI KLINIK PRATAMA RAWAT INAP MEGA BAGUS CLINIC 1 WATUKUMPUL PEMALANG JAWA TENGAH) - Ike Mega Puspita,; Erliany Syaodih,; Kahar Mulyani, (Journal of Innovation Research and Knowledge, 2025)
The clinic is a provider of basic medical services as a health facility consisting of health workers and medical personnel. Pratama Mega Bagus Clinic 1 Clinic is the only clinic in Watukumpul District, Pemalang Regency, Central Java, which consists of 15 villages based on population data, a total of 75,106 people, so the need for health service facilities in Watukumpul District is very high. For this reason, the researcher conducted research on the development strategy of the mega bagus clinic 1 inpatient primary clinic in order to achieve complete, affordable and qualified health services and facilities. In this study, the researcher will analyze the Clinical Development Strategy Using the Importance Performance Analysis Method Based on Patient Perception. The population in this study is patients enrolled in MBC1 clinics based on patients receiving treatment in January – March 2025.To calculate the level of conformity between the level of importance and the level of patient satisfaction. The results of the analysis of the IPA method obtained items in quadrant A are Tangible, Empaty, and Responsivnes parameters, namely those that discuss the layout and area of the building and the limitations of the rooms, which are obtained with low values